Differences between male and female mandibular length growth according to panoramic radiograph - Azhari Azhari; Berty Pramatika; Lusi Epsilawati (Majalah Kedokteran Gigi Indonesia, 2019)
Evaluation of the mandible was used for age and sex determination in the forensic field and it established the treatment planning in dentistry. The present study aims to determine mandibular length growth on male and female group aged   9-25 years old using panoramic radiograph. The research was conducted using analytical cross-sectional design method. The subject of this research was 412 panoramic radioraphs of patients aged 9-25 years old. It involved a totalsamples of 207 males and 205 females. This research was conducted from May to October 2017 in RSGM Padjadjaran University Bandung to meassure the length and height of mandibula from the point in condyleus to mentone. The MannWhitney test results showed a significant difference in mandibular length between men and women and no significant difference between the right andleft mandibular length in men and women. There is a difference between male and female mandibular length growth, in which the increase of growth of mandibular length in female is earlier than that of male. Male mandibular length is greater than female.